2020
DOI: 10.1038/s41586-020-2214-z
|View full text |Cite
|
Sign up to set email alerts
|

The mutational landscape of normal human endometrial epithelium

Abstract: All normal somatic cells are thought to acquire mutations. However, characterisation of the patterns and consequences of somatic mutation in normal tissues is limited. Uterine endometrium is a dynamic tissue that undergoes cyclical shedding and reconstitution and is lined by a gland-forming epithelium. Whole genome sequencing of normal endometrial glands showed that most are clonal cell populations derived from a recent common ancestor with mutation burdens differing from other normal cell types and manyfold l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
332
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 382 publications
(375 citation statements)
references
References 57 publications
(34 reference statements)
19
332
2
1
Order By: Relevance
“…This hypothesis seems well supported by two recent studies wherein individual endometrial glands were laser-captured from different areas within the endometrium of the same patient. Both studies suggest that different glands harbored different mutations [34,35]. These studies and our own results are also consistent with the findings by Mutter et al (2014) [20],where PTEN-loss appears zonally in single, or small clusters of, glands (Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This hypothesis seems well supported by two recent studies wherein individual endometrial glands were laser-captured from different areas within the endometrium of the same patient. Both studies suggest that different glands harbored different mutations [34,35]. These studies and our own results are also consistent with the findings by Mutter et al (2014) [20],where PTEN-loss appears zonally in single, or small clusters of, glands (Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 92%
“…These studies and our own results are also consistent with the findings by Mutter et al (2014) [20],where PTEN-loss appears zonally in single, or small clusters of, glands (Supplementary Figure S1). Therefore, although our study represents broader sampling of the endometrium and mutations, our observations and those of others [34,35] are consistent with driver mutations, such as KRAS G12 mutations, occurring in small, clonal pockets throughout the uterus. Furthermore, it seems likely that acquisition of these mutations provides sufficient selective advantages to expand within an entire gland of affected endometrial cells, allowing this population to be detectable by our methods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cancers of the colorectum and endometrium are the predominant types associated with germline and somatic POLE/POLD1 mutations 16,17,45 . Similar to intestinal crypts, endometrial glands are clones derived from a single recent ancestral stem cell and whole genome sequencing of a gland reveals the mutations present in that ancestral cell 29,46 . Twelve endometrial glands dissected from a 60 year-old carrying a POLE L424V germline mutation showed elevated rates of SBS accumulation (177/year vs. 29/year in normal individuals) and ID (13/year vs. <1/year in normal individuals) (Fig 3a).…”
Section: Mutagenesis In Other Tissuesmentioning
confidence: 99%
“…Structural variants were called using the BRASS algorithm (https://github.com/cancerit/BRASS) as previously described 1 . Calls were filtered using AnnotateBRASS (https://github.com/MathijsSanders/AnnotateBRASS) as previously described 5 .…”
Section: Structural Variantsmentioning
confidence: 99%